Penerapan Pembelajaran Berdiferensi di Sekolah Menengah Kejuruan (SMK) - Aulia Raisah; Alvin Maulana Al-Farizy; Kusuma Dewi; Maulana Fikri; Mohamad Irkham Maulana; Nyenyep Sriwardani; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
Vocational high school graduates are the biggest contributor to the Highest Unemployment Rate Indonesia in 2021. One of the factors causing this is the low quality of learning. Efforts to improve the quality of learning in vocational high schools can be done by carrying out learning that favors students, namely by carrying out differentiated learning. However, the implementation process in the vocational high school environment is still hampered by teachers' lack of understanding of the application of differentiated learning. This research aims to describe the implementation of differentiated learning in vocational high schools. The research uses a descriptive qualitative research approach with literature study methods from books and scientific articles in various national and international journals. Differentiated learning is learning that is carried out by paying attention to students' abilities, interests and learning styles. The stages of implementing differentiated learning in vocational high schools are carrying out diagnostic assessments, making differentiated learning plans, implementing differentiated learning, and implementing differentiated learning assessments. The success of learning is if the teacher can carry out his role well. Differentiated learning needs to be carried out in the vocational high school environment in order to improve the quality of graduates who have the attitudes, knowledge and skills needed in DU/DI in the 21st century.